Human leucocyte antigens profiling in Malay female patients with systemic lupus erythematosus: are we the same or different - Selvaraja, Malarvili; Too, Chun Lai; Tan, Lay Kim; Koay, Bee Tee; Abdullah, Maha; Md Shah, Anim; Arip, Masita; Amin Nordin, Syafinaz (BMJ Publishing Group, 2022)
Objective SLE is a heterogeneous autoimmune disease, in terms of clinical presentation, incidence and severity across diverse ethnic populations. We investigated the human leucocyte antigens (HLA) profile (ie, HLA-A, HLA-B and HLA-C, HLA-DRB1, HLA-DQA1, HLA-DQB1, HLA-DPA1 and HLA-DPB1) in Malaysian Malay female patients with SLE and determined the generalisability of the published HLA risk factors across different ethnic populations globally including Malaysia. Methods One hundred Malay female patients with SLE were recruited between January 2016 and October 2017 from a nephrology clinic. All patients were genotyped for HLA-A, HLA-B, HLA-C, HLA-DRB1, HLA-DQA1, HLA-DQB1, HLA-DPA1 and HLA-DPB1 alleles using PCR sequence-specific oligonucleotides method on Luminex platform. A total of 951 HLA genotyped population-based Malay control subjects was used for association testing by means of OR with 95% CIs. Results Our findings convincingly validated common associations between HLA-A∗11 (OR=1.65, p=3.36×10 -3, corrected P (Pc)=4.03×10 -2) and DQB1∗05:01 (OR=1.56, p=2.02×10 -2, Pc=non-significant) and SLE susceptibility in the Malay population. In contrast, DQB1∗03:01 (OR=0.51, p=4.06×10 -4, Pc=6.50×10 -3) were associated with decreased risk of SLE in Malay population. Additionally, we also detected novel associations of susceptibility HLA genes (ie, HLA-B∗38:02, DPA1∗02:02, DPB1∗14:01) and protective HLA genes (ie, DPA1∗01:03). When comparing the current data with data from previously published studies from Caucasian, African and Asian populations, DRB1∗15 alleles, DQB1∗03:01 and DQA1∗01:02 were corroborated as universal susceptibility and protective genes. Conclusions This study reveals multiple HLA alleles associated with susceptibility and protection against risk of developing SLE in Malay female population with renal disorders. In addition, the published data from different ethnic populations together with our study further support the notion that the genetic effects from association with DRB1∗15:01/02, DQB1∗03:01 and DQA1∗01:02 alleles are generalised to multiple ethnic populations of Caucasian, African and Asian descents.